Report of a Regional Workshop on the Dissemination of Agricultural Policy Information in the Mass Media - Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2006)
How can information and public relation officers assist journalists? By pointing to some worthwhile features; by releasing studies and research on the agriculture sector; studies on agriculture and how it can alleviate poverty? ...